Animal Tracking Berbasis Internet of Things - Arta, I Kadek Cahyadi; Febriyanto, Andrian; Nugraha, Ida Bagus Made Harisanjaya Adi; Widharma, I Gede Suputra; Purnama, Ida Bagus Irawan (Jurnal Teknologi Elektro; Vol 21 No 1 (2022): ( Januari - Juni ) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2022.v21i01.P02, 2022)
Animal husbandry is an activity of breeding and rearing carried out with a cage or a loose system. Loose livestock systems are commonly found in the Nusa Tenggara region, and some areas in Bali. This type of farm is difficult to monitor so it is vulnerable to theft. In addition to the possibility of theft, this livestock grazing system also has many other risks, one of which is the loss of cows either because they are lost or trapped in some places. Therefore, it is necessary to develop a tracking device that is able to monitor the presence of these livestock. This research aims to implement internet of things (IoT) for monitoring livestock or pets using GPS, NodeMCU ESP 8266, Firebase and Kodular. Data in the form of latitude and longitude values obtained by the GPS module will be sent to Firebase via a WiFi network. That data is then displayed in the Kodular application in latitude, longitude coordinates, and markers on maps. In addition, this tracking device that can be worn around the neck of the animal is equipped with an LED light that aims to monitor the position of livestock at night so that the position of them can be seen when it is dark. Keywords — Animal Tracking, Firebase, GPS, IoT, Kodular